(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Under flooding of territories is one of the most urgent geoecological problems, both in the construction development of the territory and in the operation of developed urban areas. Underflooding as a technogenic process initiates an emergency situation, where damage occurs to the foundations of buildings, structures and the environment. The authors used hydrogeological modeling tools and GIS technologies to obtain predictive characteristics of the development of the flooding process and to assess the geoecological situation for the operational development of protective measures.